COVID-19 Has Gone, But Not Its Cardiac Sequela: A Case Report - Mohammad, Masmahathir; Laksono, Sidhi (Fakultas Kedokteran Universitas Malikussaleh, 2024)
Nearly 3 years have passed since the WHO declared COVID-19 as a pandemic. The pandemic left some problems, including cardiac, even after it has gone. Myocarditis is a common cardiac complication among COVID-19 infections. We present an interesting case of a 23-year-old male admitted with chronic heart failure after COVID-19 infections. A 23-Years Old Male patient came to our emergency department (ER) with Heart Failure (HF) symptoms and signs. He had history of flu like symptom, with positive COVID marker 3 weeks prior to admission. Patient was a sailor with history of healthy lifestyle, no cardiovascular risk factor and normal medical checkup result. Cardiomegaly with LVH configuration appeared in chest x-ray. The ECG 12-lead showed sinus bradycardia with PVC multifocal and episode of Torsade de Pointes auto convert. Echocardiography revealed reduced of Ejection Fraction (EF). Patient also had history of recurrent hospital admission with ADHF within 6 months. Cardiac MRI was done to distinguish the etiology of heart failure which support the diagnosis of non-ischemia cardiomyopathy caused by chronic myocarditis. From those data, we conclude that the etiology of heart failure in this patient was due to chronic myocarditis related Covid-19 infection. Myocarditis in post COVID-19 condition is an uncommon but still possible condition that needs to be considered. This case report emphasizes the etiology of HF must be sought in all cases, because its recognition can direct the therapy and influence the prognosis of these patients.